Valuation: The art and science of corporate investment decisions - Titman, Sheridan; Martin, John D. (Noida (Uttar pradesh) Pearson India education services Pvt. Ltd., 2022)
The Art and Science of Corporate Investment Decisions provides an up-to-date, integrated treatment of the valuation of investment opportunities. Taking both industry practice and recent advances in valuation methods into consideration, this text introduces students to a broad spectrum of valuation approaches and equips them to make wise investment decisions.